2020
DOI: 10.33963/kp.15078
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of omega fatty acids and polyphenols and its relationship with the levels of inflammatory markers in men with chronic coronary syndrome after percutaneous coronary intervention

Abstract: It has been established as an independent prognostic factor for CVD. 3 Furthermore, it can be used as a predictor of acute and long-term death after percutaneous coronary intervention (PCI). 4 Similarly to the PLR, the NLR can be calculated based on complete blood count. It has been reported to have a prognostic value in CVD and is regarded as an independent predictor of cardiovascular death and long-term mortality in patients after PCI. 5 C-reactive protein is an acute-phase protein produced by the liver

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Taken together, the study by Sut et al 3 is an important contribution to the current knowledge on the dietary effects on inflammation in general and, in particular, on the role of the omega-6 / omega-3 PUFA ratio as The association of a higher ratio of dietary omega-6 / omega-3 PUFAs with inflammation reported by Sut et al 3 may hence potentially reflect an imbalance between proinflammatory and proresolving mediators derived from omega-6 and omega-3 PUFAs, respectively. Indeed, several downstream PUFA -derived lipid mediators have been shown to directly regulate the atherosclerotic process.…”
supporting
confidence: 57%
See 4 more Smart Citations
“…Taken together, the study by Sut et al 3 is an important contribution to the current knowledge on the dietary effects on inflammation in general and, in particular, on the role of the omega-6 / omega-3 PUFA ratio as The association of a higher ratio of dietary omega-6 / omega-3 PUFAs with inflammation reported by Sut et al 3 may hence potentially reflect an imbalance between proinflammatory and proresolving mediators derived from omega-6 and omega-3 PUFAs, respectively. Indeed, several downstream PUFA -derived lipid mediators have been shown to directly regulate the atherosclerotic process.…”
supporting
confidence: 57%
“…stratifying the study population by a dietary ratio of omega-6 to omega-3 PUFAs revealed significantly higher CRP levels in subjects with the ratio higher than 4:1. 3 These results indicate that the relative intake of omega-6 and omega-3 PU-FAs may reveal significant associations with inflammation in CAD. The latter assumption is supported by studies in healthy volunteers showing that a high omega-6 / omega-3 PUFA ratio is associated with increased levels of inflammatory biomarkers such as CRP or tumor necrosis factor α.…”
mentioning
confidence: 74%
See 3 more Smart Citations